ACUTE VARICEAL BLEED IN CIRRHOTIC PATIENTS: FACTORS INFLUENCING CLINICAL OUTCOME - Soban Abu Khifs; Zoobia Hussain; Rubab Munawar; Zara Sagheer; Muhammad Shaheryar Khan; Ammar Farooq; Swetha Sakthivel (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: The purpose of this study was to identify the clinical outcome and contributing factors of acute variceal haemorrhage in cirrhotic individuals.Study Design: Retrospective studyPlace and Duration: The study was conducted by collecting data from medicine departments of different hospitals during the period from July 2022 to June 2023.Methods: Total 215 patients with variceal bleed were presented in this study. Based on laboratory, clinical and imaging results, cirrhosis was diagnosed. The Baveno III consensus report was used to identify acute variceal haemorrhage, inability to control bleeding, and rebleeding. Rate of mortality related to uncontrolled bleeding was assessed.Results: There were 142 (66.04%) males and 73 (33.95%) females among all cases. 37 (17.2%) cases had age 18-30 years, 72 (33.5%) had age 31-40 years, 55 (25.6% ) patients had age 41-50 years and 51 (23.7%) cases had age >50 years. We found failure to control bleed in 27 (12.5%), re-bleeding in 31 (14.4%) cases. Diabetes was found in 88 (40.9%) cases. There were 58 instances (26.04%) of hepatocellular carcinoma and 35 cases (16.3%) of portal vein thrombosis (PVT). The presence of diabetes mellitus and active bleeding at the time of endoscopy were predictors of failure to control bleed, while the presence of diabetes mellitus and serum bilirubin >3 mg/dL were predictors of in-hospital re-bleed. Mortality was found in 19 (8.8%) cases.Conclusion: The presence of diabetes mellitus, active bleeding during endoscopy, and bilirubin levels that are greater than 3 mg/dL were revealed to be negative prognostic markers for initial control of variceal haemorrhage as well as recurrent bleed in patients with cirrhosis.